Impacts of urban solid waste disposal on soil and water in Macapá and Santana municipalities - Amapá (Research, Society and Development, 2022)
The inadequate final disposal of solid waste is a common problem in most Brazilian cities, reflecting the precariousness of the basic sanitation system, especially urban cleaning services and solid waste management, generating great socioeconomic and environmental impacts in the country. The northern region of Brazil has the worst data on basic sanitation coverage and correct disposal of solid waste with great possibilities of contamination of environments due to this problem. Thus, the objective of the present work was to evaluate the physical-chemical and bacteriological parameters of surface and groundwater from the sanitary landfill in the municipality of Macapá and the old dump in the municipality of Santana, located in the State of Amapá, to check if they meet the standards established in CONAMA Resolutions No. 357/2005 and No. 274/2000. The levels and distribution of eleven heavy metals in the soil of these areas were also evaluated. Soil and water samples were collected in October 2020 and, later, analyzes of these parameters were carried out in the laboratory. The results obeyed the values determined by CONAMA Resolution 420/2009, showing that most parameters were within the normal range, except for some points that showed high BOD, color and turbidity. The work represented a basic instrument to support decision-making by municipal managers regarding interventions/improvements in these areas of final disposal of solid waste, aiming to minimize the impacts of these deposits on water and soil quality and, consequently, to present standards in accordance with environmental legislation on the subject.